Detecting negative ions on board small satellites. Issue 4 (10th April 2017) - Lepri, S. T.; Raines, J. M.; Gilbert, J. A.; Cutler, J.; Panning, M.; Zurbuchen, T. H.
Abstract: Recent measurements near comets, planets, and their satellites have shown that heavy ions, energetic neutral atoms, molecular ions, and charged dust contain a wealth of information about the origin, evolution, and interaction of celestial bodies with their space environment. Using highly sensitive plasma instruments, positively charged heavy ions have been used to trace exospheric and surface composition of comets, planets, and satellites as well as the composition of interplanetary and interstellar dust. While positive ions dominate throughout the heliosphere, negative ions are also produced from surface interactions. In fact, laboratory experiments have shown that oxygen released from rocky surfaces is mostly negatively charged. Negative ions and negatively charged nanograins have been detected with plasma electron analyzers in several different environments (e.g., by Cassini and Rosetta), though more extensive studies have been challenging without instrumentation dedicated to negative ions. We discuss an adaptation of the Fast Imaging Plasma Spectrometer (FIPS) flown on MErcury Surface, Space ENvironment, GEochemistry and Ranging (MESSENGER) for the measurement of negatively charged particles. MESSENGER/FIPS successfully measured the plasma environment of Mercury from 2011 until 2015, when the mission ended, and has been used to map multiple ion species (H + through Na + and beyond) throughout Mercury's space environment. Modifications to the existing instrument design fits within a 3U CubeSat volume and would provide a low mass, low power instrument, ideal for future CubeSat or distributed sensor missions seeking, for the first time, to characterize the contribution of negative particles in the heliospheric plasmas near the planets, moons, comets, and other sources. Key Points: Surface interactions with dust grains in the heliosphere and near the moon can produce anions The contribution of anions to the heliosphere and lunar environment is largely unknown AIPS is a small compact, yet capable anion sensor for use on small satellites